The Ethical and Economic Case Against Sweatshop Labor: A Critical Assessment - Powell, Benjamin 1978-; Zwolinski, Matt (2012)
During the last decade, scholarly criticism of sweatshops has grown increasingly sophisticated. This article reviews the new moral and economic foundations of these criticisms and argues that they are flawed. It seeks to advance the debate over sweatshops by noting the extent to which the case for sweatshops does, and does not, depend on the existence of competitive markets. It attempts to more carefully distinguish between different ways in which various parties might seek to modify sweatshop behavior, and to point out that there is more room for consensus regarding some of these methods than has previously been recognized. It addresses the question of when sweatshops are justified in violating local labor laws. And it assesses the relevance of recent literature on coercion and exploitation as it applies to sweatshop labor. It concludes with a list of challenges that critics of sweatshops must meet to productively advance the debate.
Keywords: Labor law; Minimum Wage; Coercion; Exploitation; Sweatshops